PENGEMBANGAN SOAL TEST PEMBELAJARAN IPAS DENGAN PENGAPLIKASIAN QUIZIZZ KELAS V SDN 02 SUNGAI RUMBAI KABUPATEN DHARMASRAYA - Ahmad Ilham Asmariyadi; Amar Salahuddin; Annisa Fitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is based on problems in the learning process, namely there are problems that the author encountered in the science and science learning process activities, namely, in the science and science teaching and learning process, students experience difficulties in understanding science and science material and also students easily get bored when working on the questions given by the teacher. This of course has a big influence on student learning outcomes. The aim of this research is to develop science learning test questions using valid, practical and effective quiziz applications. The development model used in this research is, ADDIE. The ADDIE model consists of five stages, namely, Analysis, Design, Development, Implementation, Evaluation. Based on the results of research on the results of the validation of the IPAS test questions carried out by six expert validators, namely teaching module validators, graphic validators, material validators, question validators and linguistic validators, an average score of 82% was obtained in the very valid category, the results of the practicality carried out by class V teacher practitioners it was obtained 94.5% and students obtained an average completion rate of 87.8% in the very practical category, while the results of the effectiveness test in the form of test questions obtained an average completion rate of 76.3% in the effective category so that The science and science learning test questions using the Quizzizz application are said to be effective so they can be used in the learning process at SDN 02 Sungai Rumbai.